(untitled) (Research, Society and Development, 2021)
The study analyzed the evolution of the adoption of agricultural technologies in Mozambique during the period 2002-2020. The data used in this work were obtained from statistical yearbooks of the agricultural sector published by the Ministry of Agriculture and Rural Development. Descriptive statistics was the main technique used for data analysis. The results show that in the analyzed period, the adoption of agricultural technologies, access to agrarian credit, affiliation to farmers’ associations reduced significantly in Mozambique. This reduction in the use of agricultural technologies occurred at a time when the Government of Mozambican designed and implemented several policies aimed at revolutionizing the agricultural sector in the country. This shows that public policies aimed at the agricultural sector face enormous challenges to achieve the objective of improving the performance of agriculture in Mozambique. Using the national average as a benchmark, the results illustrate that the percentage of farms using improved technologies was relatively high in Tete province and very low in Zambézia province. Thus, it is recommended that future studies should investigate the causes of the widespread discontinuity in the use of technologies, as well as the factors that contribute to the provinces showing a significant discrepancy in the adoption of these technologies. The positive experience of Tete province can be used to leverage the adoption of technologies in other provinces, especially in Zambézia province.